Hydrothermally synthesized nanoparticles of zinc peroxide and their structural description. - García Ruíz, Alejandro; Escobedo, A.; Aguilar Hernández, Alberto Issac; Esparza, Rodrigo; Pérez, R. (2011)
Also, a description of the structural characteristi.cs of these nanoparticlcs will be presented. The nanoparticles can be used as the supported active phase for photocataIytic applications, as has been recentlypublished in the literature. The hydrothermal synthesis is based in dehydrated zinc acetate as the precursor using temperatures of 100 OC. The structural anaIysis of the obtained nanoparticles has been performed using X-ray di:ffraction tochniques with a subsequent Rictveld refinement afilie pattem. Tbis allows obtaining refined values aftbe cell parameters and the approxima.te crystallite sizes (10-20 nm) and also gives an insigbt on the morphology aftbe nanoparticle (truncated cube). Some high resolution electron microscope images are also presented and their structural results are compared with those obtained through the X -ray diffraction studies.